Osteofibrous dysplasia of the tibia: the importance of deformity in surveillance. (1st February 2022) - Dala-Ali, Benan; Donnan, Leo; Masterton, Gary; Briggs, Lydia; Kauiers, Cyrus; O'Sullivan, Mark; Calder, Peter; Eastwood, Deborah M.
Abstract : Aims: Osteofibrous dysplasia (OFD) is a rare benign lesion predominantly affecting the tibia in children. Its potential link to adamantinoma has influenced management. This international case series reviews the presentation of OFD and management approaches to improve our understanding of OFD. Methods: A retrospective review at three paediatric tertiary centres identified 101 cases of tibial OFD in 99 patients. The clinical records, radiological images, and histology were analyzed. Results: Mean age at presentation was 13.5 years (SD 12.4), and mean follow-up was 5.65 years (SD 5.51). At latest review, 62 lesions (61.4%) were in skeletally mature patients. The most common site of the tibial lesion was the anterior (76 lesions, 75.2%) cortex (63 lesions, 62.4%) of the middle third (52 lesions, 51.5%). Pain, swelling, and fracture were common presentations. Overall, 41 lesions (40.6%) presented with radiological deformity (> 10°): apex anterior in 97.6%. A total of 41 lesions (40.6%) were treated conservatively. Anterior bowing < 10° at presentation was found to be related to successful conservative management of OFD (p = 0.013, multivariable logistic regression). Intralesional excision was performed in 43 lesions (42.6%) and a wide excision of the lesion in 19 (18.8%). A high complication rate and surgical burden was found in those that underwent a wide excision regardless of technique employed. There was progression/recurrence in nine lesions (8.9%) but statistical analysis found no predictive factors. No OFD lesion transformed to adamantinoma. Conclusion: This study confirms OFD to be a benign bone condition with low rates of local progression and without malignant transformation. It is important to distinguish OFD from adamantinoma by a histological diagnosis. Focus should be on angular deformity, monitored with full-length tibial radiographs. Surgery is indicated in symptomatic patients and predicted by the severity of the initial angular deformity. Surgery should focus more on the deformity rather than the lesion. Cite this article: Bone Joint J  2022;104-B(2):302–308.